Measurement approaches for improved decision-making [soundrecording] - Wedgeworth, Robert (Los Angeles, Calif. CREDR Corp., 1974)
Discusses the importance of measurement, its technique and application to decision-making. It also presents implications of measurement to library standards and education.
Tape 1 (50 min.). Side A. Introduction -- The Importance of measurement / Robert Wedgeworth -- Objectives of the session / Gerald M. Born -- Issues of measurement / Ernest R. DeProspo (con't on Side B) -- Tape 2 (1 hr. 10 min.) . Side A, Techniques of measurement / Ellen O. Altman -- Applying measurement to decision-making / Kenneth E. Beasley (con't onTape 3) -- Tape 3 (45 min.). Question and answer session -- Tape 4 (45 min.). Side A. Implications of measurement: an introduction / F. William Summers -- Library standards / Rose Vainstein -- Side B. Public libraries / Allie Beth Martin -- Tape 5 (50 min.). Side A. Academic libraries / Robert P. Haro -- School libraries / Evelyn Daniel (con't on Side B) -- Side B. Library education / Jane B. Robbins -- Tape 6 (50 min.). Summary -- Question and answer session (con't on Side B)
American Library Association, 92nd annual conference. Audio cassette library for professional librarians.
Keywords: Decision-making -- Management -- Congresses; Libraries, University and College -- Measurement -- Congresses; Library education -- Measurement -- Congresses; School libraries -- Measurement -- Congresses; Library science; Management